2005
DOI: 10.1021/ja0512881
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Inhibition and Denaturation of α-Chymotrypsin with Amino Acid-Functionalized Gold Nanoparticles

Abstract: Water-soluble gold nanoparticles bearing diverse l-amino acid terminals have been fabricated to probe the effect of receptor surface on protein surface binding. The interaction of these nanoparticles with alpha-chymotrypsin (ChT) was investigated by activity assay, gel electrophoresis, zeta-potential, circular dichroism, and fluorescence spectroscopy. The results show that both electrostatic and hydrophobic interactions between the hydrophobic patches of receptors and the protein contribute to the stability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
248
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 250 publications
(256 citation statements)
references
References 51 publications
(46 reference statements)
7
248
1
Order By: Relevance
“…2C) (23). Derivative 2 or 3 was equilibrated with C4-AuNP in dichloromethane for 4 d, according to published procedures (24). The precipitated ligand-AuNP conjugate 4 or 5 was collected via filtration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2C) (23). Derivative 2 or 3 was equilibrated with C4-AuNP in dichloromethane for 4 d, according to published procedures (24). The precipitated ligand-AuNP conjugate 4 or 5 was collected via filtration.…”
Section: Resultsmentioning
confidence: 99%
“…The negative control, 3, was constructed in a similar manner as 2 with 2-chlorotrityl resin loaded with Fmoc-Gly-OH, Fmoc -7-aminoheptanoic acid and 3-(t-butoxycarbonylthio) propanioc acid. The AuNP-ligand conjugate was synthesized according to a procedure described previously (36). To conjugate a small amount of biotin onto AuNP 4 or 5, C4-AuNP (6 mg) was combined with derivative 2 (10 mg) or 3 (8 mg) and thiol-biotin (2 mg; Nanoscience Instruments, CMT015).…”
Section: Methods (A Detailed Version Is Provided As Supporting Informmentioning
confidence: 99%
“…Rotello's group has addressed these two points in a series of recent papers, first looking at the release of thiolated ligands in the presence of the glutathione peptide (present at millimolar concentration inside living cells); [26,27] then looking at the denaturation and inactivation of chymotrypsin by gold nanoparticles capped with alkane-thiol ligands eventually terminated with amino acids. [28,29] The latter studies provided fundamental insights into peptide-capped nanoparticle interactions with proteins; for example, demonstrating that hydrophobic amino acid side chains present on a nanoparticle surface can contribute to the stabilization of an adsorbed protein. Wang et al demonstrated the preparation of DNA, biotinylated, and bifunctional peptidecapped gold nanoparticles using mixed peptide monolayers composed of CALNN, CALNNGKbiotinG, and a CALNN-DNA conjugate.…”
Section: Peptide Self-assembled Monolayersmentioning
confidence: 99%
“…[14,15] Finally, gold nanoparticles functionalized with amino acids have been introduced for protein binding and concomitant denaturation. [16][17][18][19] Deliberate and specific interference with synthetic agents, however, has been coined as "high-hanging fruit in drug discovery", [20] and few examples exist that do not rely on library screens. [21][22][23] Several molecular imprinting technologies have been tried on proteins but still suffer from low non-imprinted polymer/molecularly imprinted polymer (NIP/MIP) ratios and incomplete protein recovery; the most promising techniques involve epitope imprinting (most often restricted to N/C termini), hierarchical imprinting, and imprinted soft nanoparticles.…”
Section: Introductionmentioning
confidence: 99%